Analysis and Evaluation of Traffic Congestion Control Methods in Touristic Metropolis Using Analytical Hierarchy Process (AHP) - Masoud Kadkhodaei; Rouzbeh Shad (Salehan Institute of Higher Education, 2018)
One of the most important issues of urban transport management in metropolitan cities is the control of traffic congestion in the central parts of the city or other densely populated areas. Typical ways to control traffic congestion in metropolitan areas are to create a prohibited traffic area, alternate traffic plan (even and odd), and congestion pricing. In this paper, these traffic congestion control methods have been compared and evaluated. The methodology of this research is analytical hierarchy analysis (AHP). Based on the results, the most effective measures for assessing traffic congestion control methods in metropolitan cities were improving traffic conditions, social welfare, reducing environmental pollution and improving the safety of intra-urban travel. The best Traffic congestion control options were also priced for traffic congestion, roaming traffic (odd and odd), and the creation of traffic barriers. The results of analyzes and paired comparisons in analytic hierarchy analysis were also obtained using “Expert choice” software.